2016
DOI: 10.1038/pr.2016.111
|View full text |Cite
|
Sign up to set email alerts
|

Associations between allergic diseases and attention deficit hyperactivity/oppositional defiant disorders in children

Abstract: Background:We aim to investigate the detailed associations between allergic diseases with attention deficit hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD) among children. Methods: Clinical information from 2,896 children enrolled in the Taiwan Children Health Study was obtained for analyses. Allergic diseases, including atopic dermatitis, asthma, and allergic rhinitis, have been evaluated based on the questions adjusted from International Study of Asthma and Allergies in Childhood. The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…23 Holmberg et al 24 studied multiple types of asthma and ADHD concluded that asthma was associated equally with attention and hyperactivity and the association was not restricted to either of the two dimensions of ADHD. Also, Yi-Tsen et al 5 demonstrated that children (aged 9-10 y old) having symptoms of asthma within the past 1 y were associated with having all dimensions of symptoms of ADHD. In our study asthma associated with attention and hyperactivity but not combined type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Holmberg et al 24 studied multiple types of asthma and ADHD concluded that asthma was associated equally with attention and hyperactivity and the association was not restricted to either of the two dimensions of ADHD. Also, Yi-Tsen et al 5 demonstrated that children (aged 9-10 y old) having symptoms of asthma within the past 1 y were associated with having all dimensions of symptoms of ADHD. In our study asthma associated with attention and hyperactivity but not combined type.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently, it has been suggested that asthma may be a risk factor for Oppositional Defiant Disorder (ODD), Attention Deficit Hyperactivity Disorder (ADHD) and Conduct Disorder (CD), that cause physical and emotional problems, long-term school absence, and social problems. 4,5 Psychological comorbidities and behavioral conditions are increasingly recognized as important determinants of asthma management and prognosis as these are associated with inadequate disease control, higher health care use, and poor quality of life. [6][7][8] Moreover, the recurrent exacerbations of asthma are associated with specific co-morbidities that require additional therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, emerging literature has shown that some individuals with ADHD have a higher concurrence of immune-related comorbidities, such as asthma and atopic dermatitis (AD); thus, an immune-related cause for ADHD has been proposed. [22][23][24][25][26][27][28] At the same time, MF nonionizing radiation exposure has been reported to have an association with the immune system. 9,29-33 Thus, it is conceivable that in utero exposure to MF nonionizing radiation may specifically increase the risk of ADHD with an underlying immune cause.…”
Section: Outcome Measurement: Adhd Diagnosis and Immune-related Comormentioning
confidence: 97%
“…Recently, researchers have paid close attention to the connection between ADHD and allergic disease (32,33). Previous reports have revealed potential associations between ADHD and allergic diseases (34)(35)(36). AE, AR, and allergic asthma are considered to be the most common chronic diseases worldwide and represent the three major clinical manifestations of atopy (37).…”
Section: Potential Relationship Between Adhd and Allergic Diseasementioning
confidence: 99%